Implementasi Metode Mind Mapping Paragraf Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak - Vioni Wijayanti; Sri Haryanto; Firdaus Firdaus (Al-Mau'izhoh, 2023)
In the Aqidah Akhlak subject, it prohibits beliefs, behavior, attitudes, and faith in Allah SWT. The aim of the research is to find out how the learning outcomes of class VIII A in the Aqidah Akhlak subject are through the application of the Paragraph Mind Mapping method.This study uses a type of quantitative research research. Research activities were carried out from November to December 2022. The sampling technique used in this study was purposive sampling. From this population, one class was taken, namely class VIII A with 32 students. The variable in the research used by the author is the use of the Paragraph Mind Mapping method. Collecting data using this test method the author gives tests in the form of individual post-tests or pre-tests prepared with the learning material that has been studied.The results showed that learning using the Mind Mapping method went well and received a positive response from students. The results of hypothesis testing obtained 5.32. Then it is compared with dk = +-2 = 16+16-2 = 30. With dk 30 and an error level of 5% then = 1.46. In this case the provisions apply if it is smaller than then accepted. It turns out that what you get is bigger (5.32>1.46 and 5.32>1.50). Because it was rejected and accepted.The suggestions in this study are that students are expected to be more active in learning both at school and at home, so that their learning is optimal. Students should be able to further improve discipline during the teaching and learning process takes place.So it can be concluded that the Paragraph Mind Mapping method can improve student learning outcomes in the Akidah Akhlak subject.